Integrasi Teori Konstruktivisme dalam Pembelajaran PAI untuk Memebentuk Karakter Siswa SMA Kelas XI Fase F - Muhammad Fajriansyah Solichin; Akmal Bagas Hastomo; Mochamad Faisal Mulyawan; Moh Wahyudi Putra; Abdul Fadhil (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Character building of students is one of the main goals in education, especially in Islamic Religious Education (PAI) learning. Integration of constructivism theory in PAI learning is one of the relevant approaches to achieve this goal. Constructivism emphasizes the active role of students in building understanding through social interaction, direct experience, and critical reflection. This study aims to explore how the application of constructivism theory can help shape the character of grade XI high school students in phase F. Using qualitative methods, this study analyzes the planning, implementation, and evaluation of constructivism-based PAI learning. The results of the study indicate that the constructivist approach encourages students to participate actively, think critically, and understand religious values ​​more deeply. This learning process has also proven effective in building positive character in students, such as responsibility, tolerance, and honesty. Integration of constructivism theory in PAI learning has great potential to support sustainable character education that is relevant to the challenges of the times.